Dynamics Of Decision Making: A Phenomenological Study Of The Choice Of Financial Management Concentration - Mustafa, Muh. Sabir; Olii, Nurhayati; Robin (PT. Maju Malaqbi Makkarana, 2024)
Many students decide to choose concentration because of pressure from other parties, such as parents, siblings, or the surrounding environment. Therefore, the purpose of this study is to explore and understand in depth the dynamics of decision-making in financial management concentration. The research was conducted with a phenomenological approach that reveals deep aspects that have not been revealed in the scientific literature so that it becomes a novelty about the dynamics of student decision-making in choosing a concentration. This research uses qualitative methodology with an interpretive paradigm and transcendental phenomenology approach. The key informants of this study were 8th students of financial management concentration. Data collection is done through participant observation, in-depth interviews, and documentation. The dynamics of decision-making regarding the choice of financial management concentration are caused by academic preferences, the impact of social interaction, and job opportunities. There are factors of friends or close people who give academic preferences, group factors that concern the impact of social interaction on the decision-making process, and personal factors related to future employment opportunities Keywords: Decision-making; Academic preferences; Impact of Social Interaction; job opportunities, Management Concentration